Positive Psychology Micro-Coaching Intervention: Effects on Psychological Capital and Goal-Related Self-Efficacy - Corbu, Alina; Peláez Zuberbühler, María Josefina; Salanova, Marisa (Frontiers in Psychology, 2021)
Positive Psychological Coaching is receiving increasing attention within the organizational field because of its potential benefits for employees’ development and wellbeing (Passmore & Oades, 2014). The main aim of this study was to test the impact of a Positive Psychological Micro-Coaching program on non-executive workers’ psychological capital, and analyze how goal-related self-efficacy predicts goal attainment during the coaching process. Following a control trial design, 60 non-executive employees (35 in the experimental group and 25 in the waiting-list control group) from an automotive industry company participated in a Positive Psychological Micro-Coaching program over a period of five weeks. The intervention was grounded in the strengths-based approach and focused on setting a specific goal for personal and professional growth. The program consisted of a group session, three individual coaching sessions, and individual inter-session monitoring. Pre, post, and four-month follow up measurements were taken to assess the impact on the study variables. Our results reveal that psychological capital increased significantly at post and follow-up times compared to baseline levels. In addition, results confirmed that goal-related self-efficacy predicted goal attainment during the micro-coaching process. Practical implications suggest that short-term positive psychological coaching is a valuable method for developing personal resources such as psychological capital and to facilitate the goal achievement in non-executive employees, in order to reach work-related goals.